2021
DOI: 10.21203/rs.3.rs-877916/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Edible Red Seaweed Campylaephora Hypnaeoides J. Agardh Alleviates Obesity and Related Metabolic Disorders in Mice by Suppressing Oxidative Stress and Inflammatory Response

Abstract: Background: The obesity epidemic has become a serious public health problem in many countries worldwide. Seaweed has few calories and is rich in active nutritional components necessary for health promotion and disease prevention. The aim of this study was to investigate the effects of the Campylaephora hypnaeoides J. Agardh (C. hypnaeoides), an edible seaweed traditionally eaten in Japan, on high-fat (HF) diet-induced obesity and related metabolic diseases in mice.Methods: Male C57BL/6J mice were randomly divi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Antioxidative phenolic compounds, such as phlorotannins from marine sources, have been reported to exhibit anti-obesity and anti-diabetic effects in animal models (Mateos et al, 2020). We have previously reported that the anti-obesity effects of brown and red seaweed consumed in Japan are related to their antioxidant and anti-inflammatory properties (Murakami et al, 2021(Murakami et al, , 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidative phenolic compounds, such as phlorotannins from marine sources, have been reported to exhibit anti-obesity and anti-diabetic effects in animal models (Mateos et al, 2020). We have previously reported that the anti-obesity effects of brown and red seaweed consumed in Japan are related to their antioxidant and anti-inflammatory properties (Murakami et al, 2021(Murakami et al, , 2022.…”
Section: Discussionmentioning
confidence: 99%